Analisis Pengaruh Kepemimpinan Visioner Terhadap Kepuasan Kerja dan Kinerja Pegawai dengan Iklim Kerja Sebagai Variabel Mediasi - Husnil Hidayat; Alizar Hasan (Ekonika : Jurnal Ekonomi Universitas Kadiri, 2024)
Leadership is necessary in running the wheels of the organization. The direction and goals of the organization must be commanded by a leader who is reliable, has a vision for the future, and has integrity. Visionary leadership is needed to answer the challenges of the organization in the future, in order to survive and develop. This study aims to determine how visionary leadership affects job satisfaction and employee performance with work climate as mediation. The research was conducted at the University of Muhammadiyah Muara Bungo with a population of 93 permanent employees. This type of research is quantitative using the SEM-PLS program, the primary data used is a questionnaire. The types of tests carried out are outermodel, discriminant validity test, iscriminant validity test, reliability test, then proceed with the inner model to see the direct and indirect effects. The results showed that visionary leadership had no positive and significant effect on job satisfaction with a t-stat value of 0.284 < 1.96 and a pvalue of 0.777> 0.05 (significant). Visionary leadership has no positive and significant effect on performance with a t-stat value of 0.549 < 1.96 and a pvalue of 0.583 > 0.05 (significant). Visionary leadership has a positive and significant effect on job satisfaction when mediated by work climate pvalue 0.000 < 0.05 (significant), and has a positive and significant effect on performance with work climate as mediation with a pvalue of 0.000 < 0.05 (significant).